Ordered Logistic Regression With Artificial Neural Network Models For Variable Selection For\r\nPrediction Of Hypertension Patient Outcomes - Farah Muna Mohamad Ghazali; Wan Muhamad Amir W Ahmad; Mohamad Arif Awang Nawi; Nor Farid Mohd Noor; Nur FatihaGhazalli; NorAzlida Aleng; Mohamad Shafiq Mohd Ibrahim; Nurfadhlina Abdul Halim (Cancer Research Institute, Sapporo Medical Univers, 2024)
Sapporo Medical Journal Volume 54, Issue 10, October 2020